Is there any relationship of serum Growth Differentiation Factor 15 and Iron Profile with Age? - Awais Amjad; Aiman Farogh Anjum (Aziz Fatimah Medical and Dental College, 2024)
Objective: To compare growth differentiation Factor-15(GDF-15), iron and ferritin levels in younger and elderly patients suffering from end stage renal disease on hemodialysis  and to determine is there any age-related change in these markers?. Methodology:This cross-sectional comparative study was conducted in the Nephrology Department of Sheikh Zayed Hospital Lahore from January 2018 to December 2018 after getting approval from Institutional Review Board of National Health Research Complex (NHRC) with vide no. F39/NHRC/Admin/IRB/372 Written consent was taken from patients.Group A has less than 60 years, while group B was with patients of greater than 60 years of age.Serum GDF-15, serum iron and ferritin of hemodialysis patients were determined by ELISA. Statistical analysis was done by SPSS 22.0  Results: The total number of patients was 140. Group A has 86 patients (40 male and 46 female). Group B had 54 patients(36 male and 17 female). Group A and Group B participants had serum median (IQR) GDF-15 levels 684(120-1604) and 2650(369-3625)pg/ml respectively, (P value  0.001) Conclusion: GDF-15 levels were significantly elevated in patients greater than 60 years of age and ferritin levels were similar in all age groups.